2017
DOI: 10.3390/polym10010021
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Films Made of Ionic Complexes of Poly(γ-glutamic acid) and Ethyl Lauroyl Arginate

Abstract: Abstract:The biocide agent LAE (ethyl α N-lauroyl L-arginate chloride) was coupled with poly(γ-glutamic acid) (PGGA) to form stable ionic complexes with LAE:PGGA ratios of 1 and 0.5. The nanostructure adopted by these complexes and its response to thermal changes were examined in detail by Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) using synchrotron radiation in real time. A layered biphasic structure with LAE filling the space between the polypeptidic sheets was adopted in these compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Signals arising from the anomeric proton of the glucuronic unit of HyA and the methylene protons of the lauroyl moiety of LAE (signals 1 and j) were used to determine the composition of the complexes. The relative area quantification of these signals revealed that the complexes have compositions very close to those used for their synthesis (Table 1), with deviations within the range that could be expected according to results obtained for other ionic complexes of HyA previously studied by us (Tolentino, Alla, Martínez de Ilarduya & Muñoz-Guerra, 2013;Gamarra, Missagia, Morató, Muñoz-Guerra, 2017).…”
Section: Chemical Characterizationsupporting
confidence: 70%
See 2 more Smart Citations
“…Signals arising from the anomeric proton of the glucuronic unit of HyA and the methylene protons of the lauroyl moiety of LAE (signals 1 and j) were used to determine the composition of the complexes. The relative area quantification of these signals revealed that the complexes have compositions very close to those used for their synthesis (Table 1), with deviations within the range that could be expected according to results obtained for other ionic complexes of HyA previously studied by us (Tolentino, Alla, Martínez de Ilarduya & Muñoz-Guerra, 2013;Gamarra, Missagia, Morató, Muñoz-Guerra, 2017).…”
Section: Chemical Characterizationsupporting
confidence: 70%
“…The FTIR spectra recorded from the LAE•HyA complexes are shown in Figure 1 data of the two components (Gilli et al, 1994;Gamarra, Missagia, Morató, Muñoz-Guerra, 2017). The spectra of the complexes include the bands characteristic of the two counterparts with relative intensities according to composition.…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have been performed to prepare hydrogels based on γ-PGA from different crosslinking agents, but probably cystamine, a disulfide-crosslinking agent, is the more effective [ 19 , 20 ]. Published results indicated that the structure and content of the selected agent determined the pore size, the crosslinking degree, the water absorption and even the degradation profile [ 12 , 13 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The next three articles reported the synthesis and electrostatic-force-induced complexation of anionic polyelectrolytes and dendrigraft poly(L-Lysine) [7], poly (γ-glutamic acid) and ethyl lauryl alginate [8], pillar [6]arene containing polyelectrolytes [9]. As shown by these studies, one of the advantages of utilizing polyelectrolytes is in the utilization of a layer-by-layer approach for the fabrication of thin films, which could be subsequently formulated for various applications, including: antibacterial films/patches.…”
mentioning
confidence: 99%